P2-S8.03 Did you hear about the 2010 STD treatment guidelines? Re-strategizing how we e-Communicate about STD guidance. (10th July 2011) - Habel, M A; Richman, L; Haecker, S; Verma, R; Meneghetti, A; Kachur, R; Collins, B; Barnes, R; Thompson, N; Workowski, K
Abstract : Background: The 2010 STD Treatment Guidelines advise physicians and other health-care providers on the most effective diagnostic evaluation, treatment regimens, prevention and vaccination strategies for STDs. CDC revises the Guidelines approximately every 4 years, using a scientific, evidence-based process. Previous communication efforts around the Guidelines have lacked structured promotion and evaluation strategies. 2010 communication efforts strove to improve dissemination of this important resource in the public and private sector using traditional and novel communication technologies. Methods: The Guidelines were released online in the MMWR on 16 December 2010. A communication plan was devised involving an email distribution campaign, development of interactive elements such as webinars, podcasts, social media (Twitter), and mobile promotional efforts through a partnership with Epocrates. Click-through rates and web metrics were tracked using SiteCatalyst and tracking codes. Results: 45 days post-launch, the 2010 Treatment Guidelines web page was viewed 107 174 times and downloaded 47, 715 times making it the second most popular download on CDC's website. An email campaign targeting more than 54, 000 individuals resulted in click-through rates well above worldwide government industry standard (3.3%); ranging from 10% to 878% suggesting that emails were forwarded or the site was bookmarked. A January 13 live webinar resulted in 3200 registrations, 827 CMEs, and 742 evaluations. A podcast featured on Medscape was viewed 12 296 times within 30 days; traffic was 3 times that of a June Chlamydia podcast. Preliminary Twitter data show that tweets were clicked on or retweeted at least 50 times during a 4-day period. A Dec 21 Epocrates DocAlert was delivered to 80 795 devices in the first 10 days, 272 857 devices by week 6, and targeted to primary care, OB/Gyn, ID, ER, urologists, etc.; 22% of responders requested detailed information and links via email or via iPhone/Android on device. Conclusions: Data suggest (see Abstract P2-S8.03 Figure 1 ) that promotion efforts were highly successful as page view spikes coincided with email and mobile campaign pushes. Campaign tracking codes and web metrics are a simple way to evaluate health communication efforts and can offer insight on how well target audiences are being reached. Likewise, public health communicators should consider mutually beneficial partnerships with organizations that can reach providers in the private sector.